Fructo-oligosaccharide intensifies visceral hypersensitivity and intestinal inflammation in a stress-induced irritable bowel syndrome mouse model - Binrui Chen; Lijun Du; Huiqin He; John J. Kim; Yan Zhao; Yawen Zhang; Liang Luo; Ning Dai (2017)
AIMTo determine whether fructo-oligosaccharide (FOS) affects visceral sensitivity, inflammation, and production of intestinal short-chain fatty acids (SCFA) in an irritable bowel syndrome (IBS) mouse model. METHODSMice were randomly assigned to daily oral gavage of saline solution with or without FOS (8 g/kg body weight) for 14 d.Mice were further assigned to receive either daily one-hour water avoidance stress (WAS) or sham-